Lactobacillus rhamnosus GG-Derived Soluble Mediators Modulate Adaptive Immune Cells - Ludwig, Irene S.; Broere, Femke; Manurung, Sarmauli; Lambers, Tim T.; van der Zee, Ruurd; van Eden, Willem (Frontiers in Immunology, 2018)
Probiotics and probiotic related nutritional interventions have been described to have beneficial effects on immune homeostasis and gut health. In previous studies, Lactobacillus rhamnosus GG (LGG) soluble mediators (LSM) have been demonstrated to exert beneficial effects in preclinical models of allergic sensitization, bacterial infection, and intestinal barrier function. In the context of allergic diseases, differentiation of dendritic cells (DC) and their interactions with T cell populations are crucial for driving tolerogenic responses. In the current project we set out to evaluate whether these LSM can modulate DC maturation and have an impact on prompting protective and/or tolerogenic T cell responses. Monocytes were isolated from PBMC of healthy blood donors and cultured in the presence of GM-CSF, IL-4 and LSM or unconditioned bacterial culture medium control (UCM) during 6 days to induce DC differentiation. Subsequently, these DCs were matured in the presence of TNF-α for 1 day, and analyzed for their phenotype and ability to induce autologous T cell activation and differentiation to model recall antigens. After 7 days of co-culture, T cells were analyzed for activation and differentiation by flow cytometry of intracellular cytokines (IFN-γ, IL-2, IL-10, and IL-17A), activation markers (CD25) and Foxp3+ expression. LSM did not alter DC numbers or maturation status. However, these DCs did show improved capacity to induce a T cell response as shown by increased IL-2 and IFN-γ producing T cell populations upon stimulation with recall antigens. These enhanced recall responses coincided with enhanced Foxp3+ expression that was not observed when T cells were cultured in the presence of UCM treated DCs. In contrast, the number of activated T cells (determined by CD25 expression) was only slightly increased. In conclusion, this study reveals that LSM can influence adaptive immune responses as shown by the modulation of dendritic cell functionality. These mechanisms might contribute to previous observed effects in animal models in vivo. Altogether, these results suggest that LSM may provide an alternative to live probiotics as a nutritional intervention in case life bacteria may not be used because of health conditions, although further clinical testing is needed